CLIMEJ — Organizational Climate Scale for Junior Enterprises: A Validation Study - Silvia Miranda Amorim; Hiago Rolla Martins; Guilherme Augusto da Silva Rodrigues; Roberth Moura de Souza; Lucas Duarte Rios Diniz; Sophia Domingues Siqueira Carvalho (RAC: Revista de Administração Contemporânea, 2025)
Objective: this article aimed to accumulate evidence of construct and criterion validity of the organizational climate scale for junior enterprises (CLIMEJ). Theoretical approach: organizational climate refers to employees’ perception of the work environment and is a widely investigated construct, but with gaps in the context of junior enterprises. Method: a total of 1,218 employees from all over the country participated in an online questionnaire. Results: exploratory and confirmatory factor analyses resulted in a scale of 56 items and 10 dimensions (workload; recognition; leadership; professional development; junior movement; relevance of the activity; control; communication; conflicts and physical space), with excellent adjustment indices [χ2(gl) = 887(1,494), p < 0.001; CFI = 0.99; TLI = 0.99; RMSEA = 0.01]. The structure showed convergence with work design, perception of organizational support, and flourishing at work. Conclusion: it was concluded that CLIMEJ is an effective measure that allows an innovative understanding of the context and of development strategies.